Sculptures on the east-facing exterior wall of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the east-facing exterior wall of the Shiva Temple. All the wall projections are adorned with sculptures. The bhadra (central projection) has a sculpture of Natesha, the intermediate projections have surasundaris (celestials), and the corner projections have dikpalas (deities for cardinal directions). The devakoshtha (niches) on the central bhadra is an ornate niche. The wall projections are not separated by recesses.